Oxidative and haemostatic effects of copper, manganese and mercury, alone and in combination at physiologically relevant levels: An ex vivo study. (April 2019) - van Rensburg, MJ; van Rooy, M; Bester, MJ; Serem, JC; Venter, C; Oberholzer, HM
Water contamination with metals due to anthropogenic activity is increasing and subsequent exposure increases the risk of associated toxicity. Exposure is not limited to a single metal but usually involves mixtures of different metals at different concentrations. Little is known about the contribution of this type of exposure, in humans, to the development of non-communicable diseases such as cardiovascular disease, and an increased risk to thrombosis. The World Health Organization has established limits for metal levels in drinking water and this includes levels for copper (Cu), manganese (Mn) and mercury (Hg). In this study, at 100X these limits, the ability of the metals' oxidative effects as catalysts of the Fenton reaction and/or ability to bind glutathione (GSH) were determined. The haemostatic effects of these metals, alone and in combination, at the World Health Organization limit were then evaluated. The ultrastructural and viscoelastic alterations of exposed ex vivo whole blood were also evaluated using scanning electron microscopy and thromboelastography ® (TEG), respectively. Cu, alone and in combination with Mn and/or Hg, induced hydroxyl radical formation and reduced GSH levels. Ex vivo exposure caused deformation of erythrocytes and accelerated platelet activation especially for Cu, alone and in combination, with Mn. Reduction in the lysis potential of the clot was also observed for all combinations, especially Cu in combination with Hg as well as Mn alone. Although the TEG findings were not statistically significant, the trends indicate that the exposure to these metals, alone and in combination, adversely affects thrombus formation in ex vivo blood, thereby potentially increasing the risk in exposed individuals for thrombosis.